Time course of effects of venlafaxine on migraine and generalized pruritus in a patient with depression. Issue 11 (16th November 2021) - Miyahara, Yu; Funahashi, Hideki; Haruta‐Tsukamoto, Ayaka; Hidaka, Hiroto; Fujimoto, Takako; Horinouchi, Akira; Nishimori, Toshikazu; Ishida, Yasushi
Abstract: Venlafaxine has potential as a therapeutic option for patients with depressive disorder, migraine, and pruritus unresponsive to antihistamines. Abstract : Venlafaxine has potential as a therapeutic option for patients with depressive disorder, migraine, and pruritus unresponsive to antihistamines.